Influence of Weight Reduction and Enhanced Protein Intake on Biomarkers of Inflammation in Older Adults with Obesity - Porter Starr, Kathryn N. (J Nutr Gerontol Geriatr, 2019)
Both aging and obesity are associated with increased levels of pro-inflammatory metabolites, while weight reduction is associated with improvements in inflammatory status. However, few studies have explored the response of key inflammatory markers to the combined settings of weight reduction in an aging population. There are also few studies that have investigated the potential impact of diet composition on inflammatory marker responses. In the MEASUR-UP trial, we evaluated changes in baseline levels of inflammatory markers with post-study levels for a traditional weight loss control group versus a group with generous, balanced protein intake. In this 6-month randomized controlled trial (RCT), older (≥60 yrs) adults with obesity (BMI ≥30 kg/m(2)) and Short Physical Performance Battery (SPPB) score of 4–10 were randomly assigned to either a traditional weight loss regimen, (Control, n=14) or one with higher protein intake (≥30 g) at each meal (Protein, n=25). All participants were prescribed a hypo-caloric diet and attended weekly support and education groups and weigh-ins. Protein participants consumed ≥30 g of high quality protein/meal, including lean and extra lean beef provided to them for two of the three meals per day. Protein intakes were 0.8 and 1.2 g/kg/day for Control and Protein, respectively. Adiponectin, leptin, C-reactive protein (hs-CRP), tumor necrosis factor-α (TNF- α), interleukin-1 (IL-1), IL-6, IL-8, serum amyloid A (SAA), vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and glycated serum protein (GSP) levels were measured at 0 and 6-month time points. At the 6-month endpoint, there was significant weight loss and decrease in BMI in both the Control (−4.8 ± 8.2 kg; −2.3 ± 2.4 kg/m(2); P=0.05) and Protein (−8.7 ± 7.4 kg; −2.9 ± 2.3 kg/m(2); P<0.0001) groups. SPPB scores improved in both arms, with a superior functional response in Protein (P<0.05). Body fat (%) at baseline was positively correlated with leptin, hs-CRP, VCAM-1, ICAM-1, and GSP. Several markers of inflammation responded to the Protein group: leptin (P<0.001), hs-CRP (P<0.01), and ICAM-1 (P<0.01) were decreased and adiponectin increased (P<0.01). There were no significant changes in any inflammatory markers in the Control arm. In the between group comparison, only adiponectin trended towards a group difference (more improvement in Protein; P<0.07). Our findings in the MEASUR-UP trial show that a weight loss diet with enhanced protein intake is comparable to an adequate protein diet in terms of weight loss success and that it can lead to improvements in inflammatory status, specifically for adiponectin, leptin, hs-CRP, and ICAM-1. These findings are important given current recommendations for higher protein intakes in older adults and justify additional study of the inflammatory impact of an enhanced protein diet. (ClinicalTrials.gov identifier: NCT01715753)